Determinação da densidade mineral e da elasticidade óssea após a aplicação de ondas de choque extracorpóreas no terceiro metacarpiano de equinos atletas - Pyles, Marcelo Damas [UNESP]; da Fonseca, Brunna Patrícia Almeida; Machado, Vania Maria de Vasconcelos [UNESP]; Yamada, Ana Lúcia Miluzzi [UNESP]; Alves, Ana Liz Garcia [UNESP] (My University, 2012)
The porpoise of this study was to evaluate the effects of extracorporeal shock waves in third metacarpus bone from healthy horses by determination of bone elasticity. It were used 20 Thoroughbred horses, male and female, with two years old, on top of training and selected as the state healthy. At the beginning of the experiment (D0), all animals were submitted for evaluation of bone elasticity held in the third metacarpus bone. The animals were divided into two groups (Control Group - CG and Experimental Group - EG). The application of extracorporeal shock wave therapy (ESWT) was performed on the right forelimb of the animals in the experimental group in the same place evaluated for bone elasticity and was used apparatus for extracorporeal therapy of waves with 0.15 mJ/mm2 energy flux density and 2000 pulses with E6R20 probe, with focus feature of the shock wave of 20 mm. The ESWT were repeated every 21 days, a total of three sessions (D0, D21 and D42). The analysis of bone elasticity determination was realized at D21, D42 and D72. The average of speed ultrasound differed between groups at D21, D42 and D72, and the animals from EG had lower bone mineral density after applications of ESWT. There was also difference in the analysis of bone mass (Z-Score) between the groups at D21 and D42, which animals from EG showed a significant decrease in bone mass. The risk of fracture was higher in animals from experimental group at D21. It was concluded that ESWT is able to promote change in bone mineral density.
Mineral density and bone elasticity determination after extracorporeal shock waves application in third metacarpus of athlete equines
Keywords: Bone elasticity; Equine; Extracorporeal shock wave; Third metacarpal; Animalia; Equidae; Phocoenidae